Assistance of human development cadres in making proposals for convergence prevention of stunting activities - Ramadhan, Kadar; Noya, Fransisca; Aminuddin, Aminuddin; Setiawan, Setiawan (Universitas Muhammadiyah Magelang, 2021)
The high prevalence of stunting has prompted the government to take preventive measures. One of them is the priority program for convergence to prevent stunting in villages through the Ministry of Village Regulation, Development of Disadvantaged Areas and Transmigration Number 11 of 2019 concerning Priority for the Use of Village Funds 2020. This regulation was followed up by the formation of a Human Development Cadre (KPM) to carry out convergence activities for preventing stunting with 1 cadre of 1 village. The problem that occurs is the lack of provision for convergence activities for KPM. This community service activity aims to provide assistance to KPM in making proposals for convergence activities. This activity was carried out in Poso Pesisir District, Poso Regency in February 2020. The target audience was 13 KPM people and 13 village midwives. In this KPM mentoring activity, village cadres and midwives succeeded in making proposals for convergence activities to prevent stunting in the village. It is hoped that the village government will follow up the proposals for convergence activities to prevent stunting into village meetings and it is agreed to be budgeted for 2021.